CD4 Response Up to 5 Years After Combination Antiretroviral Therapy in Human Immunodeficiency Virus-Infected Patients in Latin America and the Caribbean. (5th June 2015) - Luz, Paula M.; Belaunzarán-Zamudio, Pablo F.; Crabtree-Ramírez, Brenda; Caro-Vega, Yanink; Hoces, Daniel; Rebeiro, Peter F.; Blevins, Meridith; Pape, Jean W.; Cortes, Claudia P.; Padgett, Denis; Cahn, Pedro; Veloso, Valdilea G.; et al.
Abstract : We describe CD4 counts at 6-month intervals for 5 years after combination antiretroviral therapy initiation among 12 879 antiretroviral-naive human immunodeficiency virus-infected adults from Latin America and the Caribbean. Median CD4 counts increased from 154 cells/mm 3 at baseline (interquartile range [IQR], 60–251) to 413 cells/mm 3 (IQR, 234–598) by year 5.